Prevention of Child Stunting Through Maternal Education with Posyandu Cadres - Evi, Nurul; Zahro, Ainin Zain; Safitri, Anggun; Nurshoba, Aurelia Marsha; Salsabila, Malinda; Evi Rizal, Nasywa Nabiilah; Samudro, Paksi; Fakhriyyah, Zahrotul; Kurniawan, Setyo Budi (Tarqabin Nusantara Group, 2023)
Stunting is a condition of failure in growth caused by failure of gain weight, disruption of linear growth, head circumference, and malnutrition that cause uncomparable height to the children and peers. In 2022, based on data from the Indonesian Nutrition Status Survey (SSGI), the prevalence of stunted toddlers in Malang City will be 18%. The main factors of this condition are mothers' lack of knowledge about nutrition, parenting patterns, health services, access to clean water sources, socio-cultural factors and incorrect breastfeeding practices. Therefore, efforts are needed to increase maternal knowledge as a form of preventing stunting cases. The aim of this activity is to increase mothers' knowledge and attitudes towards stunting and MPASI in children. The method in this project based learning activity is carried out in several stages, there are the planning stage, implementation stage, and evaluation stage. In this activity, a pretest and posttest were carried out, as well as delivering the material using power point media. The results of the base learning project for Posyandu mothers on street Raya Candi II RW 2, Sukun, Malang City showed that there was an increase in knowledge